Association of the nutritional risk index recorded prior to allogeneic hematopoietic cell transplantation with the clinical prognosis in children - Hitomi Yonesu; Satoru Hamada; Hideki Sakiyama; Shinobu Kiyuna; Tokiko Oshiro; Nobuyuki Hyakuna; Koichi Nakanishi (eJHaem)
Abstract Introduction The nutritional risk index (NRI), calculated using serum albumin levels and body weight ratio is a known prognostic factor in adult hematopoietic cell transplantation (HCT). However, its usefulness in pediatric HCT settings remains unclear. Methods In a retrospective study, we examined pre‐transplant NRI impact on outcomes in 82 pediatric patients undergoing allogeneic HCT. Results The 2‐year non‐relapse mortality (NRM) rate was 7.94% (95% confidence interval [CI], 3.05%–19.8%) and 30.8% (95% CI, 16.7%–52.2%) in the high and low NRI groups, respectively (p = 0.0037). Conclusion We found that poor nutritional status prior to pediatric HCT led to a worse prognosis, including increased NRM.